SynRad v1.0: a radar forward operator to simulate synthetic weather radar observations from volcanic ash clouds - V. Nair; A. Mohanathan; M. Herzog; D. G. Macfarlane; D. A. Robertson (Geoscientific Model Development, 2025)
In this work, SynRad, a new radar forward operator for the Active Tracer High-Resolution Atmospheric Model (ATHAM) volcanic plume model is introduced. The operator is designed to generate synthetic radar signals from ground-based scanning weather radars for volcanic ash clouds simulated by ATHAM. A key novelty of SynRad is a ray-tracing module that traces radar beams from the antenna to the ash cloud and calculates path attenuation due to hydrometeors and ash. The operator is designed to be compatible with the one-moment microphysics scheme in ATHAM, but it can easily be extended to other one- or two-moment schemes in ATHAM or any weather prediction model. The operator can be used to test candidate locations at which to operationally deploy portable high-frequency or multi-frequency (from long to short wavelength) scanning radar(s). An optimal frequency or frequencies (for a multi-frequency radar) can be identified that balance the trade-off between a stronger return signal and the increased path attenuation that comes at these higher frequencies. A case study of the eruption of the Raikoke volcano in 2019 is used to evaluate the performance of SynRad. The measurement process of a C-band radar is simulated using SynRad, and the operator was able to generate realistic fields of the equivalent radar reflectivities, echo tops, and vertical maximum intensities. Even though higher-frequency microwave weather radars (K-band and higher) have been used to observe volcanic activity, they may not operate in scanning mode. Ideally, higher-frequency microwave radars will be designed and constructed specifically for monitoring volcanic eruptions. This is certainly possible in the coming years, making feasibility studies on the capability of higher-frequency radars timely.